# Pre Calculus

posted by Josh

using the factor theorem to show that x-c is a factor of P(X) for the given values of c, and factor

1. P(x)=x3-5x^2+8x-4; c=1

1. drwls

x^3 -5x^2 +8x -4 = (x-1)(x^2 -4x +4)
= (x-1)(x-2)^2

## Similar Questions

1. ### Maths

The question is "Show that z-2 is a factor of P(z)= z^3+mz^2+(3m-2)z-10m-4 for all values of m. For what values of m is (z-2)^2 a factor of P(z)?
2. ### Using the factor Theorem

use the factor theorem to determine whether x-c is a factor of f(x) f(x)=x^3+8x^2-18x+20; x-10 I have a doubt in my answer, i determined that x-10 is not a factor... am i right?
3. ### Math

Use the Factor Theorem to determine whether x-3 is a factor of P(x)=2x^3-5x^-9 . Specifically, evaluate P at the proper value, and then determine whether x-3 is a factor. P(_)=__ also pick which one applies x-3 is not a factor of P(x) …
4. ### pre calculus

Use the remainder theorem to find the remainder when f(x) is divided by x -2. Then use the factor theorem to determine whether x -2 is a factor of f(x) f(x) = 2x^5 + 6x^4 - x^2 - 7x - 12
5. ### calculus-can someone please help me with this ques

I have two questions if someone can PLEASE help. 1.solve the equation in the real number system. x^4+11x^3+24x^2-23x+35=0 **Please show work** 2.Use the remainder theorem to find the remainder. When f(x)is divided by x-3. Then use …
6. ### math

solve 6x^3-13x^2+x+2=0 using a graphing calculator. then use your answer to write the given function in factored form. (do not use the factor theorem to factor this.) (6 marks)
7. ### math ergent please

3. Factor x^4-3x^3-11x^2+3x+10 completely using the factor theorem. (5 marks) SHOW ME ALL THE STEPS PLEASE.
8. ### Maths (factor theorem)

9x^2 6xy 4y^2 is a factor of 27x^3 - 8y^3, find the other factor.
9. ### Pre Calculus

If f(x)=-4x^3 +5x^2 +8 and c=-2 is c a factor of x?
10. ### itc c++

can any one please dry run this code #include<iostream> using namespace std; int main() { intnum,factor=1,temp; cout<<"Enter any integer value"<<endl; cin>>num; //number given by the user is 10123. temp=num; …

More Similar Questions